EAACI taskforce position paper: evidence for autoimmune urticaria and proposal for defining diagnostic criteria. Issue 1 (15th November 2012) - Konstantinou, G. N.; Asero, R.; Ferrer, M.; Knol, E. F.; Maurer, M.; Raap, U.; Schmid‐Grendelmeier, P.; Skol, P. S.; Grattan, C. E. H.
Abstract An autoimmune subset of chronic spontaneous urticaria is increasingly being recognized internationally, based on laboratory and clinical evidence that has accrued over the last 20 years. This evidence has been reviewed by a taskforce of the Dermatology section of the European Academy of Allergy and Clinical Immunology. Functional autoantibodies in chronic urticaria (CU) patient sera have been demonstrated against IgE and FcεRIα by basophil and mast cell histamine release assays and by basophil activation assays. Antibody specificity has been confirmed by immunoassay, but there is a poor correlation between functionality and immunoreactivity. Approximately 25% of CU patients have a positive basophil histamine release assay and show autoreactivity (a positive autologous serum skin test), whereas 50% are negative regarding both. Functionality of CU sera appears to be complement dependent on mast cells but not exclusively on basophils. Basophil activation by CU sera is predominantly restricted to IgG1 and IgG3 subclasses. Circumstantial evidence for CU being an autoimmune disease comes from an observed association with other autoimmune diseases, a strong association between serum functionality and HLA‐DR4 haplotype and the good response of CU patients to immunotherapies. It was proposed that a study should be undertaken to prospectively validate potentially relevant clinical criteria (from the history, examination and routinely available clinical investigations) against a new 'gold standard' for the diagnosis of ACU (positive autoreactivity, functional bioassay and immunoassay) to define preliminary criteria sets for the diagnosis of ACU based on clinical and laboratory features with highest individual sensitivity and specificity.